Whose Journey to Self-Reliance? Participation in the Journey to Self-Reliance and the Land-Grant Imaginary - Lia R. Kelinsky-Jones; Kim L. Niewolny (Journal of International Agricultural and Extension Education, 2021)
Land-grant university and civil society development actors have long partnered with local and global communities to eliminate food insecurity. Despite the common aim of addressing food insecurity as a wicked problem, their approaches and designs differ in scope and scale. Similarly, levels of local stakeholder participation in agricultural development historically vary reflecting the complexity in relinquishing hierarchal decision-making power. In this pilot study, we investigated how participation is framed within the United States Agency for International Development’s (USAID) policy, “The Journey to Self-Reliance”. Subsequently, we sought to understand the implications of this framing on land-grant universities’ agricultural development aims in addressing global food security. We drew upon Fairclough’s Critical Discourse Analysis and Pretty’s typology of participation in sustainable agriculture to analyze the inaugural speech launching the policy framework by the former USAID administrator. We also held two focus groups with development actors at two land-grant universities. Findings indicate local participation of governments, citizens, and civil society to be important. However, governmental participation may be contingent on accountability to both USAID and the private sector indicating an increased commitment to neoliberal ideology. The focus group themes identify self-reliance and its journey as prescriptive and at times, neocolonial, raising questions about participatory possibilities. The final theme illustrates land-grant praxis from participants as they advance visions for centering local partner needs through more equitable decision-making and resource sharing. We conclude with considerations for future research to more deeply understand the implications of “The Journey to Self-Reliance” policy through a CDA lens.
Keywords: Agro-ecology; Extension; Theory and Practice; Qualitative Research; Community Development